Theology for crisis: practical theology and the practice of giving an account - Benac, Dustin D. (Practical theology, 2023)
Practical theology has historically identified the problems that confront individuals and communities as a principal site for theological reflection and research. While such attention to the contextual concerns that confront communities of faith has (re)centred the field, reducing practical theology to reflection on problems underestimates the complexity of the crisis/es individuals and communities face. Secondarily, a limited focus on problems understates the field’s interpretive consequence by reducing practical theology to pragmatic reflection on the social realities that surround faith. In contrast to existing focus on problems, ‘crisis’ provides a category that permits social description and theological reflection about the interplay between divine and human activity in the ordering of a common life. Representing an experience of being brought up short, crisis requires new interpretive horizons and invites individuals and communities to cultivate the practice of giving an account. First, I introduce the crisis in the field as the reduction of theological reflection to problems alone. Second, I defined ‘crisis’, noting how crisis differs from trauma, tragedy, and characteristic damage. Third, and finally, I draw upon Luke-Acts to illustrate how this reframing of practical theology around crisis requires the practice of giving an account of divine and human encounter.